Antibiograms and molecular subtypes of methicillin-resistant Staphylococcus aureus in local teaching hospital, Malaysia - Thong, Kwai Lin; Junnie, J.; Liew, F.Y.; Yusof, M.Y.; Hanifah, Y.A. (The Korean Society for Applied Microbiology, 2009)
The objectives of this study were to determine the antibiotypes, SCCmec subtypes, PVL carriage, and genetic diversity of MRSA strains from a tertiary hospital. Sixtysix MRSA strains were selected randomly (2003, 2004, and 2007) and tested for the Panton-Valentine leukocidin gene, mecA gene, and SCCmec type via a PCR. The antibiograms were determined using a standard disc diffusion method, and the genetic diversity of the isolates was determined by PFGE. Thirty-four antibiograms were obtained, with 55% of the 66 strains exhibiting resistance to more than 4 antimicrobials. All the isolates remained susceptible to vancomycin, and low resistance rates were noted for fusidic acid (11%), rifampicin (11%), and clindamycin acid (19%). The MRSA isolates that were multisensitive (n=12) were SCCmec type IV, whereas the rest (multiresistant) were SCCmec type III. Only two isolates (SCCmec type IV) tested positive for PVL, whereas all the isolates were mecA-positive. The PFGE was very discriminative and subtyped the 66 isolates into 55 pulsotypes (F=0.31-1.0). The multisensitive isolates were distinctly different from the multidrug-resistant MRSA. In conclusion, no vancomycin-resistant isolate was observed. The Malaysian MDR MRSA isolates were mostly SCCmec type III and negative for PVL. These strains were genetically distinct from the SCCmec type IV strains, which were sensitive to SXT, tetracycline, and erythromycin. Only two strains were SCCmec IV and PVL-positive. The infections in the hospital concerned were probably caused by multiple subtypes of MRSA.